Formation of pedagogical values in moral education teachers based on an axiological approach - Boburmirzo Nomonjon-o‘g‘li Gaybullayev (Science and Education, 2026)
This article examines the pedagogical foundations, methodological principles, and practical significance of forming pedagogical values in Moral Education teachers based on an axiological approach. In modern educational reforms, special attention is paid to the development of teachers’ professional competence, moral culture, and value-oriented pedagogical activity. The axiological approach serves as an important methodological basis for strengthening teachers’ professional values, humanistic worldview, spiritual culture, and ethical responsibility.